PENGARUH PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY, DAN STRUKTUR KEPEMILIKAN TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN TEKNOLOGI DI BEI - Marshela Sutrisno; Yulia Setyarini (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Tax aggressiveness is a form of action taken by taxpayers in carrying out their tax planning. The purpose of doing so is to reduce taxable income. The aggressive action in question can be either positive or negative. This study aims to examine whether or not the influence of profitability, leverage, capital intensity, and ownership structure on tax aggressiveness. This study has a sufficient population of 49 technology companies listed on the IDX. Producing 88 samples in this study consisting of technology companies that meet the criteria during the period 2020 to 2023. The type of data used is secondary data obtained from the official website of each company or from the IDX website. The results of this study stated that the first variable profitability has no effect on tax aggressiveness. Then the second variable, leverage, has no effect on tax aggressiveness. The third variable capital intensity has no effect on tax aggressiveness. The fourth variable of institutional ownership affects tax aggressiveness. The last variable, namely managerial ownership, has an effect on tax aggressiveness.